Determination of mitragynine bound opioid receptors - Baharuldin, Mohamad Taufik Hidayat; Apryani, Evhy; Mohamad, Nabishah; Mohd Moklas, Mohamad Aris; Fakurazi, Sharida; Adzhar, Muhammad Farhan (American-Eurasian Network for Scientific Information, 2010)
Mitragyna Speciosa Korth from Rubiaceae family is a tropical plant indigenous to Southeast Asia particularly in Thailand, Peninsular of Malaysia and Indonesia. The leaves have been used by natives for their opium-like effect and cocaine-like stimulant ability to combat fatigue and enhance tolerance to hard work. This study is designed to examine the binding affinity and selectivity of mitragynine towards opioid receptors namely µ-, δ-, and κ-receptors and the density of those opioid receptors in brain tissues, spinal cord, duodenum, ileum and vas deferens. Our results suggest that mitragynine has a high affinity to the 9-opioid receptors and brain has the highest density of opioid receptors.